Editorial - Lizárraga Salas, Frambel (INTER DISCIPLINA, 2019)
The migratory processes are consubstantial to the evolution of the social groups that have constituted our civilization throughout its history. The navigation trips of the late fifteenth century were the substrate of the first attempt at globalization of Western culture. They brought as a consequence (among others) that the heirs of the cradle of our specie were enslaved by the descendants of those who emigrated from it. A very particular case is the one in North America. The dispossession of an immense area of northern Mexico by the United States, drew an imaginary line (although coercive) that divided areas with homogeneous cultures north and south of it. The deterioration of living conditions in Mexico, a consequence of unequal economic exchange, has generated a migraory phenomenon that is perceived more as a vindication of alienated rights than as a challenge to the status quo.